Assessment of impaired glomerular filtration rate and associated factors in South West Ethiopia: a cross-sectional study - Bisrat Fikadu Habtu; Gizachew Ayele; Habtamu Belay; Seid Abrar; Dereje Abebe; Nigus Chekole (BMC Nephrology, 2024)
Abstract Introduction Currently, kidney disease is an increasing major health problem worldwide. It is expected to be the 5th ranked cause of death by 2040. If it is early detected, further complication caused by kidney disease will be minimized. An assessment of impaired glomerular filtration rate (eGFR) has potential aids in early identification and treatment of kidney disease. However, in hospital practice instead of using eGFR, direct measurement of serum creatinine level is used for assessing renal function. Hence, this study is aimed to assess the magnitude and associated factors of impaired glomerular filtration rate among admitted patients in Wolkite University Specialized Teaching Hospital (WKUSTH). Objective To assess the magnitude and associated factors of impaired glomerular filtration rate in WKUSTH, Ethiopia 2023. Method Institutional based cross-sectional study with secondary data was conducted. 338 participants were selected by a convenient sampling technique. Epidata 3.1 version for data entry and SPSS version 20 for data analysis was used. Bivariate analysis was used to screen candidate variables for multivariate analysis. In the multivariate analysis a P-value < 0.05 were considered statistically significant. Results The study enrolled 338 patients admitted to WUSTH. Seventy (20.7%) (95% CI: 16.6–25.4%) of them had impaired eGFR according to Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation and Modification of Diet in Renal Disease (MDRD-4). older age (AOR 3.38, 95% CI; 1.31, 8.71), hypertension (AOR 17.8, 95% CI; 7.75, 41.22), anemia (AOR 2.51, 95% CI; 1.11, 5.83) DM (AOR 11.2, 95% CI; 4.11, 30.73), and high BMI (AOR 7.56, 95% CI; 3.16, 18.08), were independently associated with impaired eGFR. Conclusions The magnitude of impaired eGFR was prevalent among adult patients admitted to WKUSTH medical ward with different medical conditions. Old age, Hypertension, Diabetes, high body mass index, and Anemia were significantly associated with impaired eGFR both in CKD-EPI and MDRD-4 equation. Estimation of GFR for all hospitalized adults with known CKD risk factors might help in early detection of CKD and prevent complications.